Rifle marksmanship a guide to M16- and M4-series weapons (Skyhorse Publishing, 2018)
Rifle Marksmanship is the newly revised, official guide to planning and executing training on the M16-series rifles (M16A1, M16A2, M16A3, and M16A4) and M4 carbine. This handbook is developed by the US Army for commanders, leaders, and instructors to help create training programs and materials for soldiers to complete the United States Army rifle marksmanship program. It offers a comprehensive guide to the specifics and capabilities of each weapon and an introduction to the fundamentals of marksmanship, followed by complete guidance through each of the five stages of rifle marksmanship training. Topics covered include: Weapon Characteristics, Accessories, and Ammunition; Range Safety and Risk Management; Preliminary Marksmanship and Mechanical Training; Advanced Optics, Lasers, and Iron Sights; 10-Meter Target Offsets and 25-Meter Zero Offsets; Training Aids, Devices, and Scorecards. Replete with information and training materials for learners and instructors, this handbook provides the guidance for all shooters, whether in combat or in hunting and recreation, to operate their rifles with deadly proficiency.